Activities to train professionals reflective on action: a proposal of competence development from practical ECTS in the special education teacher training degree - Josep Valls; Jordi Coiduras; M; Ramona Ribes; M. Àngels Marsellés; Gloria Jové; M. Jesús Agulló (Revista Electronica Interuniversitaria de Formación del Profesorado, 2009)
Educational experiences in Nursery and Primary schools of our local area are essential resources to train future teachers. During the second and third year of the teacher training degree in Educational needs, our students are continually involved in these schools. Throughout these teaching placements they have to develop an activity in relation to the theoretical knowledge acquired at University. The students are asked not only to observe the experienced professionals, but also to act as teachers, designing and putting into practice different experiences with children aged six to twelve. Later, they will have to analyse and evaluate these experiences using different strategies.